2020
DOI: 10.1177/0003489420937744
|View full text |Cite
|
Sign up to set email alerts
|

Occult Metastasis in Laryngeal Squamous Cell Carcinoma: A Systematic Review and Meta-Analysis

Abstract: Objective: The incidence of occult metastasis (OM) in laryngeal squamous cell carcinoma (SCC) is still widely debated. In this systematic review, we aim to determine the rate of OM in laryngeal SCC, its impact on recurrence, and the role of elective neck dissection (END) in the management of the clinically negative neck. Methods: A systematic review of the English-language literature in Web of Science, Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…Another interesting finding in our study was that the T stage had no influence on both the OS and CSS of patients. We believe this is because the head and neck squamous cell carcinoma is characterized by a higher rate of lymph node metastasis; therefore, the degree of tumor invasion may have little impact on the prognosis of the disease [28][29][30]. Surprisingly, we found that marital status plays an important role in the disease prognosis, with married patients having higher cancer survival rates than unmarried patients [31].…”
Section: Discussionmentioning
confidence: 72%
“…Another interesting finding in our study was that the T stage had no influence on both the OS and CSS of patients. We believe this is because the head and neck squamous cell carcinoma is characterized by a higher rate of lymph node metastasis; therefore, the degree of tumor invasion may have little impact on the prognosis of the disease [28][29][30]. Surprisingly, we found that marital status plays an important role in the disease prognosis, with married patients having higher cancer survival rates than unmarried patients [31].…”
Section: Discussionmentioning
confidence: 72%
“…As regional lymph node metastases have a high influence on treatment and prognosis, a decision on the treatment of the neck always needs to be considered. In HNSCC, there is a high risk of occult CLN metastasis in clinically nodal negative necks with incidences of 30% in oropharyngeal [ 19 ], 23.7% in hypopharyngeal [ 20 ] and 20.5% in laryngeal squamous cell carcinoma (SCC) [ 21 ]. It is not always an easy decision in patients with a clinically nodal negative neck between overtreatment in terms of a complete or even a contralateral neck dissection with risks such as bleeding or intraoperative nerve damage and missing occult metastasis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastases (LNMs) are common at the time of diagnosis in head and neck squamous cell carcinomas (HNSCCs), while the rate of occult LNMs is up to 20% in some subtypes of HNSCC [ 1 , 2 , 3 , 4 , 5 ]. The presence of LNMs bears a major prognostic influence, with an estimated 50% reduction in overall survival in nodal negative vs. nodal positive HPV-negative HNSCC [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%